Drivers of large carnivore density in non‐hunted, multi‐use landscapes. Issue 1 (6th January 2023) - Devlin, Allison L.; Frair, Jacqueline L.; Crawshaw, Peter G.; Hunter, Luke T. B.; Tortato, Fernando R.; Hoogesteijn, Rafael; Robinson, Nathaniel; Robinson, Hugh S.; Quigley, Howard B.
Abstract: Protected areas serve as population strongholds for many large carnivores, with multi‐use landscapes along their borders forming the front‐lines of wildlife conservation. Understanding large carnivore population dynamics within working landscapes is difficult where anthropogenic mortality is high and unregulated. This study focused on working ranches, where killing jaguars ( Panthera onca ) and their prey was prohibited, to gain insight into jaguar population potential across multi‐use landscapes. Faced with forest fragmentation, presence of domestic livestock, and dynamic land‐use practices, we expected jaguar populations in working landscapes to be predominantly male and transient, with low cub production, and inflated population densities in remnant forest patches, versus protected areas where we expected native forest habitat and stable jaguar territories. Using camera traps and spatial‐capture recapture analyses, we observed that male jaguars demonstrated larger‐scale movements and were more detectable than females (0.07 ± 0.01 SE vs. 0.02 ± 0.01 SE) in both working and protected landscapes. Female jaguars in ranches traveled farther than females in parks. Carnivore density increased with forest cover and wild prey activity, decreased with domestic prey activity, and was marginally higher in ranches (4.08 individuals/100 km 2 ± 0.73 SE) than in parks (3.59 individuals/100 km 2 ± 0.64 SE). Females outnumbered males in both landscapes (2.20–2.60 females/100 km 2 vs. 1.60 males/100 km 2 ), although local male density reached up to 11.00 males/100 km 2 in ranches (vs. 3.50 males/100 km 2 in parks). While overall jaguar density was patchier in protected areas ( x ̿ = 0.69 parks, 0.54 ranches), inter‐annual patchiness was higher within ranches (Moran's I = 0.49–0.60 ranches, 0.69–0.70 parks), reflecting changes in cattle management. Despite major habitat alterations, working landscapes can support carnivore densities equivalent to (or exceeding that of) unmodified forest habitat, provided that wildlife‐tolerant ranching practices are maintained.